Hematological responses in juveniles after training at moderate altitude - Ohno, H.; Kim, Ch. K.; Kim, J. H.; Jung, Y. S.; Bae, S. Y.; Toshinai, K.; Miyazaki, H.; Esaki, K.; Takemasa, T.; Kinugasa, T.; Kizaki, T.; Hitomi, Y.; et al. (Advances in Exercise and Sports Physiology, 2004)
The aim of the current study was to investigate the effects of moderate-altitude training on hematological parameters including erythropoietin (EPO) and 2,3-diphos-phoglycerate (2.3-DPG) in juveniles. Eight young male and three female skiers, aged 9-19 years, participated in this experiment. The training protocol consisted of 4-5-h skiing, 6 times/week, for 5 weeks, at an elevation of 2,700 m or of 3.500 m (for the last 3 days) in summer. Living quarters were at 2,100 m for 2 weeks and at 2,700 m for the following 3 weeks, respectively. Their blood samples were collected at sea level 3-4 days before and after the training. As anticipated, there were significant (P<0.05) increases in red blood cell count, hemoglobin (Hb), and hemotocrit after moderate-altitude training. Also, blood 2,3-DPG concentration rose significantly (P<0.05) after training indicating a shift of the Hb dissociation curve to the right, whereas serum EPO level showed a significant(P<0.05) decrease. The decrease in EPO level inversely P<0.05) correlated with the change in 2,3-DPG concentration after training. The results obtained suggest that moderate-altitude training has benefical effects on hematolofical parameters in juveniles, probably improving red cell oxygen transport.